Deconstructing Desire: Sexism and Power in Maroon 5's Animals - Sanjaya, Firman Hadi; Samanik, Samanik; Maretha, Carla (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study employs a qualitative content analysis to examine Maroon 5's "Animals" as a multi-layered narrative that explores themes of obsession and desire. The lyrics frame desire as a predatory act, blurring the lines between attraction and obsession, while simultaneously raising critical concerns about objectification and gendered power dynamics. Through close analysis of the song"™s lyrics, particular attention is given to phrases and metaphors that invite multiple interpretations. The analysis is anchored in Jacques Derrida's theory of deconstruction, which reveals how the song destabilises traditional binary oppositions, such as predator and prey. This approach illuminates the nuanced interplay of dominance and vulnerability within the song's narrative. The findings suggest that "Animals" offers an intricate commentary on complex human relationships, while also reflecting broader societal attitudes toward gender and power. The study contributes to the growing discourse on media representation and encourages critical engagement with popular culture as a means to challenge and dissect prevailing cultural  narratives.